Nanoparticles: A Vaccine Adjuvant for Subcutaneous Administration - Pitaksuteepong, Tasana (Asian Health, Science and Technology Reports, 2005)
Subcutaneous administration is the most appropriate route for delivering an antigen because the antigen can drain directly from the injection site to lymph nodes where immunocompetent cells reside. Nanoparticles, having a size ranging from 1-1,000 nm, are considered as the most promising adjuvant for subcutaneous immunization. This article is aimed to review the studies relating to the investigation of nanoparticles efficiency to elicit the immune response following subcutaneous administration and to determine if the nanoparticles are actually capable to enhance immune response. Factors influencing the achievement and the magnitude of immune induction are also included.